A three-step process of manganese acquisition and storage in the microalga Chlorella sorokiniana. (1st December 2022) - Vojvodić, Snežana; Dimitrijević, Milena; Žižić, Milan; Dučić, Tanja; Aquilanti, Giuliana; Stanić, Marina; Zechmann, Bernd; Danilović Luković, Jelena; Stanković, Dalibor; Opačić, Miloš; Morina, Arian; Pittman, Jon K; et al.
Abstract: Metabolism of metals in microalgae and adaptation to metal excess are of significant environmental importance. We report a three-step mechanism that the green microalga Chlorella sorokiniana activates during the acquisition of and adaptation to manganese (Mn), which is both an essential trace metal and a pollutant of waters. In the early stage, Mn 2+ was mainly bound to membrane phospholipids and phosphates in released mucilage. The outer cell wall was reorganized and lipids were accumulated, with a relative increase in lipid saturation. Intracellular redox settings were rapidly altered in the presence of Mn excess, with increased production of reactive oxygen species that resulted in lipid peroxidation and a decrease in the concentration of thiols. In the later stage, Mn 2+ was chelated by polyphosphates and accumulated in the cells. The structure of the inner cell wall was modified and the redox milieu established a new balance. Polyphosphates serve as a transient Mn 2+ storage ligand, as proposed previously. In the final stage, Mn was stored in multivalent Mn clusters that resemble the structure of the tetramanganese–calcium core of the oxygen-evolving complex. The present findings elucidate the bioinorganic chemistry and metabolism of Mn in microalgae, and may shed new light on water-splitting Mn clusters. Abstract : Manganese ions first bind to phosphate moieties in membrane and mucilage, then to intracellular polyphosphates, and finally accumulate in the microalgal cell in the form of multivalent Mn–O–Ca clusters.